2015
DOI: 10.1111/cei.12486
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental and bicompartmental knee osteoarthritis show different patterns of mononuclear cell infiltration and cytokine release in the affected joints

Abstract: SummaryIt is still controversial which cell types are responsible for synovial inflammation in osteoarthritic (OA) joints. The aim of this study was to quantify the mononuclear cell populations and their cytokines in patients with different knee OA subtypes. Synovial membrane (SM), synovial fluid (SF) and peripheral blood (PB) were harvested from patients with unicompartmental (UC) and bicompartmental (BC) knee OA. Frequencies of mononuclear cells were assessed by flow cytometry in PB and SM. Naive SF samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 51 publications
(144 reference statements)
9
67
0
1
Order By: Relevance
“…Two recent studies [19■,20■] employ flow cytometry to study synovial membrane infiltration; both found CD14+ macrophages most abundant, followed by CD4+ T lymphocytes. In the second study [20■], pain scores available from a subset of patients correlated with proportions of synovial CD4+ cells, indicating a role for infiltrating T cells in osteoarthritis pain that needs further investigation.…”
Section: Local Infiltration Of Cellsmentioning
confidence: 99%
“…Two recent studies [19■,20■] employ flow cytometry to study synovial membrane infiltration; both found CD14+ macrophages most abundant, followed by CD4+ T lymphocytes. In the second study [20■], pain scores available from a subset of patients correlated with proportions of synovial CD4+ cells, indicating a role for infiltrating T cells in osteoarthritis pain that needs further investigation.…”
Section: Local Infiltration Of Cellsmentioning
confidence: 99%
“…These findings suggest that activation of synovial macrophage is required for the production of MMPs leading to cartilage damage (82)(83)(84)(85). Natural killer cells have also been obtained from synovial tissues of patients undergoing total joint replacements, but the mechanism of pathogenesis has not yet been elucidated in detail (86).…”
Section: Correlation Between Synovitis and Oamentioning
confidence: 99%
“…However, in the context of bone lytic diseases involving chronic inflammation, such as periodontitis and rheumatoid arthritis, infiltrations of not only B and T cells but also of macrophages are observed (6,7). It is true that macrophages are the most abundant immune cells found in the synovial membrane in osteoarthritis (8) and in synovial fluid in rheumatoid arthritis (9), outnumbering T and B cells. Therefore, it is plausible that osteoclast differentiation is affected by local factors produced by infiltrating lymphocytes, especially macrophages.…”
mentioning
confidence: 99%